Kualitas Pelayanan Kesehatan Poli Gigi Rumah Sakit Kota Palembang - Menti Youlanda (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2018)
Health service in hospital currently focuses on patient satisfaction that service quality becomes indicator of service used. The problem of this study was how about the health service quality at dental clinic of Myria Hospital Palembang. The aim was to know the health service quality at dental clinic of Myria Hospital Palembang. The study method was descriptive quantitative using questionnaire. The samples were 90 respondents by using purposive sampling technique. Data were analyzed by using descriptive statistic, factor analysis, and regression with significance 0,1. Output statistic result of Anova linear regression was 0,086 that indicated significant relation between health service quality and patient satisfaction. Health service quality at dental clinic of Myria Hospital Palembang is already good.